Facial nerve paralysis: a clinical study - Sudhakaran, Shilpa K.; Madayambath, Sagesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: A facial paralysis is one of the most emotionally traumatic deficits a person can experience. It is essential to understand the cause and nature of nerve injury and undertake proper measures for restoration and rehabilitation of facial symmetry. The present study was conducted to evaluate the various aetiologies of lower motor neuron facial paralysis that presented to our department. The aim of the present study is to investigate into the demographic data and etiology associated with peripheral facial nerve paralysis and to assess the site of lesion, severity grade and treatment outcome of peripheral facial nerve paralysis. Methods: A prospective longitudinal study conducted in a tertiary care hospital, over a time period of one and a half years from November 2014 to April 2016. All the patients were assessed regarding the time of onset of symptoms, rapidity of progression, duration and completeness of paralysis. Topo diagnostic tests were done to assess the site of lesion and response to treatment monitored. Results: The most common cause for LMN facial nerve paralysis was external trauma and Bell’s palsy. The mean age group was 37.5 years with a male preponderance. Majority of the lesions were suprageniculate and had a House Brackmann grade IV severity score. Conclusions: Peripheral facial paralysis showed a good response to treatment and timely intervention would result in a full or partial recovery at the end of a follow up.